2012
DOI: 10.7314/apjcp.2012.13.11.5421
|View full text |Cite
|
Sign up to set email alerts
|

Monosomal Karyotypes among 1147 Chinese Patients with Acute Myeloid Leukemia: Prevalence, Features and Prognostic Impact

Abstract: A monosomal karyotype (MK), defined as ≥2 autosomal monosomies or a single monosomy in the presence of additional structural abnormalities, was recently identified as an independent prognostic factor conveying an extremely poor prognosis in patients with acute myeloid leukemia (AML). In the present study, after excluding patients with t(15;17), t(8;21), inv(16) and normal karyotypes, 324 AML patients with cytogenetic abnormalities were the main subject of analysis. The incidences of MK were 13% in patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(39 reference statements)
3
9
0
Order By: Relevance
“…CK lost its prognostic significance when MK was taken into consideration for prognostic evaluation. In concordance to Breems et al [129], negative effect on OS of single monosomy has been demonstrated by Yang et al [132] in Chinese AML population.…”
Section: Complex Chromosomal Aberrations (Ck) and Monosomal Karyotypementioning
confidence: 56%
“…CK lost its prognostic significance when MK was taken into consideration for prognostic evaluation. In concordance to Breems et al [129], negative effect on OS of single monosomy has been demonstrated by Yang et al [132] in Chinese AML population.…”
Section: Complex Chromosomal Aberrations (Ck) and Monosomal Karyotypementioning
confidence: 56%
“…The prevalence of MK in AML is 20%-30% in non-Asian patients 7,9,20 and less than 20% in Asian patients. 21 The most frequent monosomies observed in AML involve chromosomes 5 and 7, 20,21 but all autosomal chromosomes have reportedly been involved. 21 In the present study, the incidence of MK in adult ALL patients was 12.8%, lower than that found in AML.…”
Section: Cytogenetic Resultsmentioning
confidence: 99%
“…21 The most frequent monosomies observed in AML involve chromosomes 5 and 7, 20,21 but all autosomal chromosomes have reportedly been involved. 21 In the present study, the incidence of MK in adult ALL patients was 12.8%, lower than that found in AML. Different from that in AML patients, the frequency of involvement of chromosomes 5 and 7 was low, and there was no predominance of any specific monosomy.…”
Section: Cytogenetic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MK+ AML yields low rates (only 20 to 30%) of CR and short remission duration yielding reported median survival of 8 to 10 months with 2 year survival less than 10% (3, 13, 20, 31, 32). The current HCT study includes only those achieving CR after induction therapy.…”
Section: Discussionmentioning
confidence: 99%